Respiratory Disorders in Complicated Cervical Spine Injury - S. A. Pervukhin; M. N. Lebedeva; A. A. Elistratov; A. V. Palmasph; I. A. Stacenko (Общая реаниматология)
Objective. Evaluating the results of respiratory therapy in patients with complicated traumatic injury of the cervical spine.Materials and methods. A retrospective comparative analysis of the clinical course was carried out in 52 patients with complicated traumatic injury of the cervical spine: group A: complete spinal cord injury (ASIA A), 37 patients and group B: incomplete injury (ASIA B), 15 patients. The severity of patients' status on integral scales, parameters of the respiratory pattern and thoracopulmonary compliance, gas composition, and acidbase status of the blood were assessed. Data on patients who required prolonged mechanical ventilation, duration of mechanical ventilation, incidence of nosocomial pneumonia, duration of stay in the ICU, time of hospital treatment, and mortality were included in the analysis. Results. The average APACHE II and SOFA scores were higher in group A patients. The development of the acute respiratory failure required longterm mechanical ventilation (more than 48 hours) in 91.4% of group A patients and in 53.3% of group B patients. Ventilatorassociated pneumonia complicated the disease in 81.3% of group A patients and 62.5% of group B patients and was accompanied by sepsis in 25% and 12.5% of cases, respectively. Statistically significant deterioration of biomechanical properties and gas exchange function of the lungs was observed in patients complicated with septic pneumonia.Conclusion. Patients with complicated ASIA A and ASIA B cervical spine injuries demonstrate the presence of respiratory failure of neurogenic origin. In addition, the infectious bronchopulmonary complications aggravated respiratory failure in patients with ASIA A injury in 70.3% versus 33.3% in patients with ASIA B. Developmentof pulmonogenic sepsis led to deterioration of the biomechanical and gas exchange functions of the lungs and increased the likelihood of unfavorable outcome of the disease in 77.8% of cases. The high incidence of respiratory disorders in patients with complicated cervical spine injury requires timely decision on ventilatory support, especially in patients with complete spinal cord injury.